Regulatory mechanisms of simulated precipitation on cbbL carbon-fixing microbial communities in the alpine source wetland - Zhang, Ni; Yang, Ziwei; Qi, Desheng; Li, Lin; Chen, Kelong; Fu, Li; Sun, Jianqing (Frontiers in Microbiology, 2025)
Global warming intensifies the hydrological processes in wetlands, thereby affecting the carbon dynamics of these ecosystems. The cbbL gene, a key gene involved in carbon fixation, is significantly influenced by changes in precipitation. In this study, precipitation manipulation treatments with 25 and 50% increases and decreases, along with a natural control, were established to assess the response of cbbL-carrying carbon-fixing microbial communities to altered precipitation in the source wetland of Qinghai Lake. Amplicon sequencing was conducted to characterize microbial community composition and dynamics. The results showed that with increased precipitation, the relative abundance of Actinobacteria exhibited a decreasing trend, while Cyanobacteria showed an increasing trend. Chlorophyta exhibited an “n”-shaped variation pattern (P < 0.05). Soil carbon and nitrogen were the most important factors influencing the cbbL carbon-fixing microbial community in the source wetland, with their concentrations decreasing as precipitation increased. The 25% increased precipitation treatment enhanced the environmental selection of cbbL carbon-fixing microbes, shifting the community assembly process from randomness to determinism. In addition, with the increase in precipitation, the network complexity and connectivity among cbbL carbon-fixing microbial species increased. In summary, reduced precipitation helps to enhance the carbon sequestration potential of the source wetland.